2011
DOI: 10.1142/s0218957711500060
|View full text |Cite
|
Sign up to set email alerts
|

Articular Sound and Clinical Stages in Knee Arthropathy

Abstract: Objective: To clarify the pathophysiology of knee arthropathy, articular sound in the knee joint was recorded using an accelerometer, vibroarthrography (VAG), during standing-up and sitting-down movements in patients with osteoarthropathy (OA) of the knees. Methods: VAG signals and angular changes of the knee joint during standing-up and sitting-down movements were recorded in patients with OA, including 17 knees with OA at KellgrenÀLawrence stage I and II, 16 knees with OA at III and IV stages, and 20 knees o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Previous studies described a difference in the frequency based on FFT7, 8 ) or signal variations (jitter and shimmer analysis)13 ) between normal knee and knees with OA. So far, however, there are no true VAG data between the femur and tibia, because it is impossible to measure areas just next to impact in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies described a difference in the frequency based on FFT7, 8 ) or signal variations (jitter and shimmer analysis)13 ) between normal knee and knees with OA. So far, however, there are no true VAG data between the femur and tibia, because it is impossible to measure areas just next to impact in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study8 ) demonstrated that a high frequency area (200−600 Hz) obtained by fast Fourier transform (FFT) is a key feature of knee OA. Another study7 ) reported that a frequency of 50−150 Hz in patients with knee OA using FFT was higher than that in age-matched elderly. FFT does not take time information into account, and therefore FFT analysis cannot be applied to investigate the relationship between knee joint motion and VAG signal frequency information.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…It is based on recording the vibroacoustic signal during movement of articular surfaces. It has been demonstrated that VAG signals generated by degenerative cartilage differ from healthy joint signals[ 17 , 18 ]. Although the VAG method is still in development, it shows repeatability in subsequent motion cycles[ 15 , 19 ] and in addition accuracy of over 90% when compared with the clinical findings made in the standard diagnostic procedures[ 11 , 20 ].…”
Section: Introductionmentioning
confidence: 99%